Evaluation Of Different Aspects of Janani Suraksha Yojana in Indore District, Madhya Pradesh - Priyanka Mahawar; Shweta Anand; Sanjay Dixit; A K Bhagwat; Salil Sakalle; Veena Yesikar (Medsci Publications, 2013)
Background: In 2005, with the goal of reducing the numbers of maternal and neonatal deaths, the Government of India launched Janani Suraksha Yojana, a conditional cash transfer scheme, to incentivise women to give birth in a health facility. Objective: A Cross-sectional study was done in Indore district from November 2008- October 2009 with the objectives to evaluate perception, utilization and administrative and financial aspects of JSY in Indore District. Methodology: A total of 265 respondents including beneficiaries of JSY, ASHA & medical officers from 5 different health centres were included. Results: Total 42.8% of beneficiaries had three antenatal checkups. ASHA motivated 49% of beneficiary for institutional delivery.60% of ASHA received training within last 6 months only. 24.8% of beneficiaries received cash just after the delivery. ASHA is the main source for creating awareness about JSY in 90% of beneficiaries in peripheral areas. ASHA accompanies beneficiaries to health centre in as much as 47% in PHC & CHC.